ANALISIS EFISIENSI PENERAPAN TRANSAKSI NON TUNAI DALAM PENGELOLAAN KEUANGAN DAERAH PADA SEKRETARIAT DAERAH KOTA METRO PROVINSI LAMPUNG - Lidanna Dian Kurnia (Universitas Muhammadiyah Metro Lampung, 2020)
Implementation of non-cash transactions in each region are different, both constraints and applications. The non-cash transaction system is considered to be more practical, efficient, easy, even able to support the economy through increased money circulation speed. The implementation of this non-cash system is one of the forms to realize the financial management that is transparent, accountable, effective and efficient. The aim of this study is empirically to know the efficiency of the implementation of non-cash transactions in regional financial management at Metro District. The research method used is a quantitative descriptive method. The results showed that the implementation of the non-cash transactions in regional financial management at Metro City, Lampung Province provides many benefits namely transactions become highly efficient and also effective. The advantage of implementing a non-cash transaction system is that the use of all transaction flows can be traced so that it is more accountable because all transactions are backed by valid proof; treasurer does not have to hold cash with varying risks of crime, loss and error counts; avoiding financial abuse in regional devices; more efficient usage of budgets and more controlled cash-in flows; improve internal control of cash management and simplify billing acceptance. In addition, non-cash transactions tend to be more cost-effective when compared to the use of cash transactions with kartal money, banknotes or coins and accelerate the implementation of book close as well as financial reporting and guaranteed reliability.Keywords: Efficiency, Non-Cash Transactions